A research study on the Sustainable Competitiveness and the Macro Economic Factors of the IT Sector in India which contributes to sustainability and the rise of social development. - ARUNACHALAM, VIVEK; FOUNTIS, ANASTASIOS (The journal of contemporary issues in business and government, 2021)
The Indian IT Sector has grown at the very fast pace and since the IT Platform becomes the base for all the other industries to evolve post new normal, India has a great advantage of developing its most competitive sector into the most profitable sector. This could be possible when the firms in the sector are able to develop their sustainability through value creation and innovation. This research studies on the PESTEL factors of India and how it influences the sector’s competitive advantage. The researchers study how the IT sectors support in the social and environment factors and contribute to sustainable development. The research emphasises on the PESTEL factors and how the emerging of new platforms of technology could pave way for new firms to be innovative and thereby contribute to overall factors of development. Competitiveness and innovation in the technology sectors could be the philosophy for survival for the IT firms and thereby the nation needs to create an overall ecosystem for the firms to breed. This research studies on different factors relating to sustainability and competitiveness and its contribution to economic prosperity. The research has been conducted by studying the top 5 IT firms out of the Fortune 500 IT firms in India. Though the research is conducted considering the global and macro economic factors that affect both the internal and external environments. The chosen firms for study have been TCS, CTS, Accenture, Capgemini and Infosys. Though the paper focusses on different aspects relating to sustainability, competitiveness and the PESTEL factors, there is an aspect of Environmental Factors that contribute to sustainable development and the impact of economic prosperity and rise of social development thereby poverty alleviation also a part indirectly linked to the idea of this chosen topic.